Association of supplementary feeding with stunting among children in Kintamani, Bangli, Bali Province - Istiana Marfianti; I Made Ady Wirawan; I Wayan Weta (Universitas Udayana, 2017)
Background and purpose: The prevalence of stunting among under-five children in Indonesia and also in Bali is high. Studies on risk factors of stunting have been widely conducted in Indonesia, however association between stunting and diet pattern is still inconsistent. The aim of this study is to examine association of supplementary feeding pattern with stunting among children aged 1-3 years. Methods: A case control study was conducted in Bangli District. A total of 48 cases and 48 controls were selected to participate in the study. Age and sex variables between cases and controls were matched. Cases and controls were selected using a systematic random sampling method from 26 health post registers in Kintamani I Public Health Centre between November and December 2016. Data were collected in March 2017 by interviewing the mother at the health post. Data were analysed using bivariate and multivariate analysis. A logictic regression was performed to calculate adjusted odd ratio (AOR). Results: Cases and controls were comparable for age (p=0.773), sex (p=0.219), mother’s education (p=0.673) and history of infectious diseases (p=0.584). Cases and controls differed in several variables: frequency, variability and type of supplementary feeding (p=0.002, <0.001 and <0.001), family income (p=0.038), poor personal hygiene (p<0.001), environmental sanitation (p=0.022) and access to clean water (p<0.001). Our analysis showed that several variables were associated with stunting among children aged 1-3 years, which included lack of supplementary feeding variability (AOR=12.45; 95%CI: 2.25-69.71), poor personal hygiene (AOR=3.52; 95%CI: 1.03-12.03), and poor access to clean water (AOR=6.49; 95%CI: 1.61-26.19). Other variables included supplementary feeding initiation, frequency of supplementary feeding, consistency or type of supplementary feeding, sex, and family income were not associated with stunting among children aged 1-3 years. Conclusions: Variability of supplementary feeding, personal hygiene, and access to clean water were all associated with stunting among children aged 1-3 years.